Study to develop a program of regional cooperation between the Caribbean Community and Japan : consultant's report - Braveboy-Wagner, Jacqueline Anne (Wagner Group New YorkUS, 1995)
Examines the strengths and obstacles to closer CARICOM-Japan relations. Suggests a framework for a regional program of activities and identifies the type of assistance available. Looks at aspects of implementation of the regional programme and focuses on the contextural framework for the development of this program with Japan.